THE BLUEST EYE: CONTROVERSIAL TOPICS OF RACISM, INCEST, AND CHILD MOLESTATION (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This scientific article delves into one of the most famous American novelist and editor Toni Morrison by exploring some new information. In terms of by examining the historical roots of her composition and highlighting the contributions of key figures in the field, a comprehensive understanding of the Toni Morrison’s way of life is presented. The article also supplies insights into the comparison along with analyze of her novels, besides the importance of that type of books explore by some plausible examples. It is natural that, by the drawn conclusions from works of the writers such as, Toni Morrison, how much they are reading in today’s modern world, they can give opportunity to further improving the level of not only thinking, but also critical way of considering something. In addition, one of the main goal is that, in calculating new concepts as well as ideas in the readers though the images in her work and the basic meaning she want to express by a number of books. Another main purpose is that, seeking though the works of such writers is to raise the spiritual level by making them think and think more deeply. This is actually the planned plan by investigating them. Though the detailed analysis of past practises and current trends, this article offers a nuanced perspective on the transformative journey of the books of Toni Morrison.